Predatory lending and the subprime crisis - Agarwal, Sumit; Amromin, Gene; Ben-David, Itzhak; Chomsisengphet, Souphala; Evanoff, Douglas D. (Journal of Financial Economics, 2014)
We measure the effect of a 2006 antipredatory pilot program in Chicago on mortgage default rates to test whether predatory lending was a key element in fueling the subprime crisis. Under the program, risky borrowers or risky mortgage contracts or both triggered review sessions by housing counselors who shared their findings with the state regulator. The pilot program cut market activity in half, largely through the exit of lenders specializing in risky loans and through a decline in the share of subprime borrowers. Our results suggest that predatory lending practices contributed to high mortgage default rates among subprime borrowers, raising them by about a third.